2010
DOI: 10.1128/cvi.00129-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Antigenic Extracts of Eurotium amstelodami in Serological Diagnosis of Farmer's Lung Disease

Abstract: In France and Finland, farmer's lung disease (FLD), a hypersensitivity pneumonitis common in agricultural areas, is mainly caused by Eurotium species. The presence of antibodies in patients' serum is an important criterion for diagnosis. Our study aimed to improve the serological diagnosis of FLD by using common fungal particles that pollute the farm environment as antigens. Fungal particles of the Eurotium species were observed in handled hay. A strain of Eurotium amstelodami was grown in vitro using selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
(28 reference statements)
0
23
0
Order By: Relevance
“…Allergy or asthma caused by ascospores has been reported for Daldinia (Herxheimer et al 1966), Leptosphaeria (Ganderton 1968;Burge et al 1985;Hasnain 1993a;Newson et al 2000;GrinnGofroń and Mika 2008), Didymella (Frankland and Gregory 1973;Jenkins et al 1981; Ackroyd and Fry 1983;Harries et al 1985;Allitt 1986;Richardson 1996;Newson et al 2000;Grinn-Gofroń and Mika 2008), Leptosphaerulina, Gibberella, Gnomonia and Chaetomium (Burge 1986) and Pleospora (Newson et al 2000). Moreover, the presence of ascospores and other fungal spores has been associated with increases in the number of emergency visits and hospital admissions for asthma (Atkinson et al 2006), and a recent study (Roussel et al 2010) shows that antigens are more abundant in ascospores than in conidia or hyphae in one species of Eurotium.…”
Section: Introductionmentioning
confidence: 92%
“…Allergy or asthma caused by ascospores has been reported for Daldinia (Herxheimer et al 1966), Leptosphaeria (Ganderton 1968;Burge et al 1985;Hasnain 1993a;Newson et al 2000;GrinnGofroń and Mika 2008), Didymella (Frankland and Gregory 1973;Jenkins et al 1981; Ackroyd and Fry 1983;Harries et al 1985;Allitt 1986;Richardson 1996;Newson et al 2000;Grinn-Gofroń and Mika 2008), Leptosphaerulina, Gibberella, Gnomonia and Chaetomium (Burge 1986) and Pleospora (Newson et al 2000). Moreover, the presence of ascospores and other fungal spores has been associated with increases in the number of emergency visits and hospital admissions for asthma (Atkinson et al 2006), and a recent study (Roussel et al 2010) shows that antigens are more abundant in ascospores than in conidia or hyphae in one species of Eurotium.…”
Section: Introductionmentioning
confidence: 92%
“…1,3-b-Glucanase-treated protein extract (BGPE) from E amstelodami ascospores was recently demonstrated to be the most efficient antigen for differentiating between patients with FLD and healthy control subjects by using an ELISA serologic test. 6 Developing a battery of standardized antigens known to cause FLD and making them available to clinicians for use in diagnosis is recommended in the report from the National Heart, Lung, and Blood Institute/Office of Rare Diseases Workshop. 7 The aim of the present study was to characterize immunogenic proteins of ascospores and to synthesize standardized recombinant antigens to improve the serologic diagnosis of FLD.…”
Section: Aspergillus Species Recombinant Antigens For Serodiagnosis Omentioning
confidence: 99%
“…The ability to differentiate between patients with FLD and exposed control subjects by using ELISAs with ascospore crude extract was evaluated in a previous study 6 and was demonstrated as follows: sensitivity, 71%; specificity, 87%, positive likelihood ratio, 5.6; negative likelihood ratio, 0.3; and area under the curve, 0.85. Sensitivity was at 89% when a score combining the results of ELISAs with the 2 recombinant antigens was used.…”
Section: Aspergillus Species Recombinant Antigens For Serodiagnosis Omentioning
confidence: 99%
“…The structures of M. immunogenum were recovered by scraping and filtration. Two M. immunogenum Ag extracts were produced: a total aqueous lyophilised extract (somatic Ag) used for ES on cellulose acetate [10,11] and a protein extract used for ELISA tests [12].…”
Section: Immunological Methodsmentioning
confidence: 99%
“…As described previously [10,12], 96-well plates (PolySorp Immunomodule; Nalge Nunc1, Rochester, NY, USA) were coated with 200 mL 1 mg?mL -1 protein Ag solution in 50 mM K 2 HPO 4 buffer (Sigma-Aldrich1), pH 8.5, at 4uC for 48 h. Excess binding sites were blocked at 37uC for 1 h with 250 mL of 50 mM NaH 2 PO 4 buffer (Sigma-Aldrich1) containing 0.5% bovine serum albumin (Sigma-Aldrich1) and 60 g?L -1 sorbitol (Sigma-Aldrich1). 100-mL serum samples diluted 1:200 were added in triplicate to all wells.…”
Section: Elisamentioning
confidence: 99%